2006
DOI: 10.1177/0340035206063903
|View full text |Cite
|
Sign up to set email alerts
|

Access to Electronic Healthcare Information Resources in Developing Countries: experiences from the Medical Library, College of Medicine, University of Nigeria

Abstract: This paper presents results from a preliminary investigation into the situation regarding access to electronic healthcare information in developing countries, focusing on the circumstances in the Medical Library, College of Medicine, University of Nigeria. A review of current literature examines broader issues around access to electronic information in developing countries, and specific issues regarding electronic healthcare information. Studies that particularly focus on the situation in Nigeria are identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…In the library, students have to choose a particular database and be more selective in the search words they use (Waldman, 2003). Watts and Ibegbulem (2006) examined some of the barriers to the use of electronic resources available at the medical library of the College of Medicine, University of Nigeria, Nsukka. Their findings revealed that lack of an adequate ICT infrastructure and affordable online access, absence of in-depth ICT skills and information searching skills among library staff and users are barriers to the use of electronic resources.…”
Section: Constraints To the Use Of Internet Resourcesmentioning
confidence: 99%
“…In the library, students have to choose a particular database and be more selective in the search words they use (Waldman, 2003). Watts and Ibegbulem (2006) examined some of the barriers to the use of electronic resources available at the medical library of the College of Medicine, University of Nigeria, Nsukka. Their findings revealed that lack of an adequate ICT infrastructure and affordable online access, absence of in-depth ICT skills and information searching skills among library staff and users are barriers to the use of electronic resources.…”
Section: Constraints To the Use Of Internet Resourcesmentioning
confidence: 99%
“…Others include; too much information on the Internet, lack of specificity, searching difficulties, inadequate ICT infrastructure, needs to acquire ICT and information seeking skills, lack of structure training, limited or hindered Internet access, relatively expensive nature of the Internet café and lack of current information materials on the Internet [33][34]25 and 35].…”
Section: Introductionmentioning
confidence: 99%
“…While EHR adoption has been low in some developed countries, the success of EHR adoption has also been low for developing countries, which are generally resource constrained (e.g. insufficient E-Health infrastructure), due to lack of (i) required ICT support, (ii) awareness among stake holders, and (iii) a drive to adopt new system or functions (Watts et al 2005;Diero et al 2006). Moreover, costs, available information technology infrastructure (including a lack of data processing facilities), and a lack of technical expertise and computer skills of staff are major issues which would need to be addressed before EHR implementation is possible (Watson, 2006).…”
Section: Background and Motivationmentioning
confidence: 99%
“…Healthcare, which spans across all ages, genders, races, culture and geographical boundaries, is an area of concern to all population. Many countries (especially developing countries) are plagued with critical healthcare issues such as chronic, infectious and/or pandemic diseases, a lack of basic healthcare programmes and facilities and a shortage of skilled healthcare workers (WHO, 2006;Watts et al 2005).…”
Section: Introductionmentioning
confidence: 99%